Guest

1∫ -1 ( x + 3) dx

1∫-1 ( x + 3) dx

Grade:12

2 Answers

Miryala Gopalakrishna
43 Points
7 years ago
integration of x+3 from -1 to 1 is equal to
(((x^2)/2)+3x) from -1 to 1
((1/2)+(3))-((1/2)-3)
=3+3
=6
 
Anusha
20 Points
7 years ago
Ans:-1-1 (x+3)dx
=[(x2 /2)+3x]-11
=[(12)/2 -(-12 )/2]+3(1-(-1))
=(1/2)-(1/2)+6
=6

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free